Career Maturity Factors of Muslim Students of Faculty of Economics in Entrepreneurship Career Planning - Yulia Novita; Cipto Hadi; Mhd. Subhan (Universitas Islam Negeri Sultan Syarif Kasim Riau Pekanbaru, 2023)
This study aims to determine the influence of Muslim students' career maturity factors on entrepreneurship career planning. Career maturity has an important role in career planning among students. The population of this study was students of the Faculty of Economics, Riau State University, namely the Riau State Islamic University and Riau State University, totaling 5,156 students. This research technique used a random sampling technique consisting of 260 samples. The data collection tool uses two instruments, namely the career maturity instrument and entrepreneurship career planning. Validity trials were carried out with 3 experts consisting of 1 expert in economics and 2 experts in career guidance and counseling. Instrument reliability test on overall career maturity Alpha Cronbach .86, career maturity attitudinal Cronbach Alpha .75 and career maturity competency Alpha Cronbach .82. Which is an entrepreneurship career planning instrument with an alpha Cronbach value of .83. Data analysis using SPSS Software Version 22.0. The research results show that in the overall career maturity descriptive, the attitude section and competency section are at a simple stage. However, in contrast to descriptive career planning, entrepreneurship is at a high stage. In addition, analysis of inference using the t-test shows that there is a significant difference between men and women, namely the career maturity of women is higher than that of men. Likewise, there is no significant difference in career planning between men and women. Whereas in the regression analysis, it was found that the results of the study gave a significant influence on the career maturity factor on entrepreneurship career planning among students, namely 82.5%. TRANSLATE with x EnglishArabicHebrewPolishBulgarianHindiPortugueseCatalanHmong DawRomanianChinese SimplifiedHungarianRussianChinese TraditionalIndonesianSlovakCzechItalianSlovenianDanishJapaneseSpanishDutchKlingonSwedishEnglishKoreanThaiEstonianLatvianTurkishFinnishLithuanianUkrainianFrenchMalayUrduGermanMalteseVietnameseGreekNorwegianWelshHaitian CreolePersian // TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster PortalBack//